Pengaruh Kompetensi SDM terhadap Kinerja Karyawan melalui Motivasi Kerja Sebagai Variabel Intervening: (Studi Pada PT Pegadaian Kantor Daerah Pemeriksaan Bojonegoro Provinsi Jawa Timur) - Bambang Sutanto; Indra Prasetyo; Chamariyah Chamariyah (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Based on research conducted by Bambang Sutanto (2025) at the Bojonegoro Regional Inspection Office at PT Pegadaian, it was found that human resource (HR) competence and availability have a significant influence on employee performance, both directly and indirectly through work motivation as an intervening variable. This research is explanatory with a quantitative approach and involved 65 respondents, and used Smart PLS (Partial Least Square) as an analysis tool. The objectives of the study include testing the influence of HR competence on employee performance, the influence of HR competence on work motivation, the influence of work motivation on employee performance, and the indirect influence of HR competence on performance mediated by work motivation. The results of the analysis show that HR competence has a positive and significant direct effect on employee performance, as well as directly increasing work motivation. Work motivation is also proven to have a significant positive effect on employee performance, emphasizing the importance of the role of motivation as a mediator. In addition, HR competence has a significant indirect effect on employee performance through work motivation, which emphasizes that increasing HR competence not only has a direct impact on productivity, but also through increasing employee intrinsic drive. These findings emphasize the importance of effective HR development strategies and empowerment programs to maximize employee performance by increasing work motivation. This approach serves as an important reference for management in designing HR policies that focus on developing employee capacity while simultaneously motivating them to achieve optimal performance.